The Use of Work-Home Practices and Work-Home Conflict: Examining the Role of Volition and Perceived Pressure in a Multi-Method Study - Delanoeije, Joni; Verbruggen, Marijke (Frontiers in Psychology, 2019)
In response to the rising number of individuals who have to combine work and home responsibilities, organizations increasingly offer work-home practices. These are HR-practices such as telework and part-time work that can help employees to combine work and home roles. However, extant research on the relationship between work-home practice use and both work-to-home conflict (i.e., work interfering with private life) and home-to-work conflict (i.e., private life interfering with work) shows inconsistent results. In this study, we posit that employees’ work-home conflict does not so much depend on whether or not they use a specific work-home practice, but rather on (1) the degree to which their (non-)use of this practice is in line with their preference (i.e., volition) and (2) the pressure they experience from the work and/or the home environment to act in another way than they prefer (i.e., perceived work pressure and perceived home pressure). Hypotheses are tested for two specific work-home practices (i.e., home-based telework and part-time work) in both a field study and an experimental between-subject vignette study. Results show that work-home conflict is affected by volition, perceived work pressure and perceived home pressure; yet, some differences were found between the two types of work-home conflict (i.e., work-to-home and home-to-work conflict) and between the two types of work-home practices. Our results nuance the dichotomy between users and non-users of work-home practices that has been dominantly used in the work-home practice literature to date and point to similar predictors of work-home conflict among both the group of users and the group of non-users. These findings may encourage researchers to examine characteristics of employees’ work-home practice use (e.g., volition, perceived pressure) in addition to the mere use of these practices when studying their effectiveness.